Determinants of dental service utilization among public elementary school teachers in a highly urbanized city in the Philippines/ Anne Margaret P. Cordero and Christeen Grace R. Lim; co-author - Cordero, Anne Margaret P.; Lim, Christeen Grace R. (Department of Community Dentistry, University of the Philippines Manila, 2016)
Introduction: A socioeconomic gradient in dental service utilization (DSU) has long been established. When economic factors are controlled, as in a particular income class, other factors affecting DSU can be identified. Examining the factors significantly associated with the DSU of public elementary schoolteachers (PES) provides insight on the DSU behavior of a major Philippine income group, to which they belong. This study determined factors affecting DSU of PES in Manila City, Philippines.